Effect of educational program based on Health Beliefs Model on self-care behaviors among Type II Diabetic Patients - أحمد, سمر; علاء طويل; ولاء اصبيره (Latakia University Journal -Medical Sciences Series, 2022)
Diabetes is a chronic disease; its treatment outcomes depends not only on medications but also on patient self-care behavior. The current study aimed to evaluate the effect of an educational program based on the health belief model on self-care behaviors among patients with type II diabetes in the city of Lattakia, using the quasi-experimental approach (pre-post). The program was applied in the eighth health center on a sample of 50 patients from both sexes were selected using the appropriate non-random sampling method. Data were collected using the Health Belief Model Questionnaire and the Diabetes Self-Management Questionnaire. The results showed that the largest proportion of patients (46%) were over the age of 60 years, and about half (48%) of them had been diagnosed with the disease more than 10 years ago. The results also showed an increase in the average axes of the health belief model (perceived susceptibility, perceived risks, perceived benefits and signs for action), statistically significantly, and perceived barriers also decreased, and the level of self-management behaviors improved from (1.65 ± 0.486) during the pre-evaluation to (1.96 ± 0.607) after applying the program with significant statistical significance (P = 0.011). Therefore, the current study recommends designing diabetes education programs based on the health belief model with a focus on raising the level of self-efficacy and removing obstacles to their implementation of the health behaviors required to prevent complications of the disease.